(untitled) (Journal of Nepal Physical Society, 2021)
The simple statistical model or simple theory of mixing has been used to study the structural behavior of cadmium based alloys at their molten state at a temperature of 800 K by computing thermodynamic functions and structural functions. The thermodynamic functions include free energy of mixing (GM), activity (a), the heat of mixing (HM), and the entropy of mixing (SM). The structural functions include concentration fluctuation in the long-wavelength limit (SGG(0)) and Warren-Cowley short-range order parameter (α1). Interchange energy or interaction energy or ordering energy (ω) was calculated for the respective alloys system and found to be positive and temperature-dependent. Based on interchange energy (ω) and coordination number (Z), theoretical values of all the functions are calculated by applying the grand partition function. All the computed values for the mentioned functions are in good agreement with experimental values. For the cadmium based alloys, viz., Cd-Zn & Cd-In, both show the segregating in nature at temperature 800 K for the concentration of range 0.1 to 0.9, however, Cd-Zn is more segregating than Cd-In.